Adaptasi Dakwah Antar Budaya Sebagai Pembentuk Identitas Muslim Melayu di Makassar - Lasido, Nur Allan; Rahman, Eka Yuliana (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
This study aims to analyze the dynamics of intercultural da'wah adaptation in the Malay Muslim community in Makassar. The background of this research is based on the lack of information about the dynamics of intercultural da'wah for ethnic Malay Muslims in Makassar, which can affect people's understanding of cultural diversity. The research method uses a qualitative approach with an ethnographic study involving participatory observation, in-depth interviews, and qualitative data analysis. The results showed that the Malay Muslim community in Makassar plays an essential role in forming cultural identity amid ethnic and religious diversity. The adaptation of intercultural da'wah is observed in the location of Malay people and places of worship that are on the crossing path of cultural and religious diversity. The Makmur Melayu Mosque, as the centre of religious activities, is located close to Chinese and Arab settlements, reflecting the contribution of intercultural da'wah in forming Malay-Muslim identity in Makassar. The process of cultural acculturation is also observed through the adaptation of language, social systems and Islamic values For example, cultural adaptation was found through cross-cultural marriages, especially among Bugis Makassar aristocrats, which contributed to the formation of identity and social structure in Makassar.